KEHIDUPAN SOSIAL EKONOMI TUKANG BECAK MOTORDI PANGKALAN KERINCI KABUPATEN PELALAWAN - MULIA, SILVIA RISKI; ", NURHAMLIN (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This thesis proposed in order to qualify a degree in Sociology. By title “Socio-Economi Life Of The Motor RickshawDriver In Pangkalan Kerinci, Pelalawan. Issues discussed in this paper is to describle the socio-economi life of the motorrickshaw driver in Pangkalan Kerinci, Pelalawan. Socio-economi life the motor rickshaw driver in Pangkalan Kerinci seethrough condition indicators of income, food, housing, health, education and the srategies used by the motor rickshaw driverto stay afloat with a minimal income.Population of this study are all pedicab motor vehicle ownership status of exitingpersonal in Pangkalan Kerinci, Pelalawan motorcycle rickshaw driver 70. Samples were taken usingn a sample census.Method used is descriptive quantitative method to analyze quantitative and qualitative data. Data screening instruments usedare observation, questionnaires and interview as well as the tabulation of data contained in a single tabulations anddiagrams.Research results in general that in doing so the writer can say that the income of the rickshaw drivers say the motoris still in its early stages can be so low that they have to strive to meet the needs of families looking for a second job. Housingconditions in general are hired by the physical condition of the cement floor, wall board and cement half away house and hasone room sometimes but there are also two rooms using room divider is plywood. When family illness usually brought to ahealth clinic or buy medicine in the shop because it is more effective and easrer to reach. Whereas in the education of childrenin the family only a small portion can continue their education to higher education. Requires minimal revenues motorcyclerickshaw drivers perfom a survival strategy is to improve exiting asset such as looking for a second job to be working wellbore or opening a small shop. Changing consumption patterns into survival strategies such as the motor rickshaw driver inbuying cheap goods.Keyword: Pedicab Motor, Socio-economic, Survival Strategies (Adaptation Strategies)